Global Impact of COVID-19 on Service Delivery and Vulnerable Populations’ Access to Dental Care - Francisco Ramos-Gomez; Thomas Gerhard Wolf; Morenike Oluwatoyin Folayan; Marcela Diaz-Betancourt; Gyanendra Kumar; Margherita Fontana; Guglielmo Campus (Taylor and Francis, 2024)
10p